Early Survivorship After Liver Transplantation: A Qualitative Study Identifying Challenges in Recovery From the Patient and Caregiver Perspective. Issue 3 (21st October 2021) - Lieber, Sarah R.; Kim, Hannah P.; Baldelli, Luke; Nash, Rebekah; Teal, Randall; Magee, Gabrielle; Desai, Chirag S.; Loiselle, Marci M.; Lee, Simon C.; Singal, Amit G.; Marrero, Jorge A.; Barritt, A. Sidney; et al.
Abstract : Survivorship after liver transplantation (LT) is a novel concept providing a holistic view of the arduous recovery experienced after transplantation. We explored components of early survivorship including physical, emotional, and psychological challenges to identify intervention targets for improving the recovery process of LT recipients and caregivers. A total of 20 in‐person interviews were conducted among adults 3 to 6 months after LT. Trained qualitative research experts conducted interviews, coded, and analyzed transcripts to identify relevant themes and representative quotes. Early survivorship comprises overcoming (1) physical challenges, with the most challenging experiences involving mobility, driving, dietary modifications, and medication adherence, and (2) emotional and psychological challenges, including new health concerns, financial worries, body image/identity struggles, social isolation, dependency issues, and concerns about never returning to normal. Etiology of liver disease informed survivorship experiences including some patients with hepatocellular carcinoma expressing decisional regret or uncertainty in light of their post‐LT experiences. Important topics were identified that framed LT recovery including setting expectations about waitlist experiences, hospital recovery, and ongoing medication requirements. Early survivorship after LT within the first 6 months involves a wide array of physical, emotional, and psychological challenges. Patients and caregivers identified what they wish they had known prior to LT and strategies for recovery, which can inform targeted LT survivorship interventions.